2019
DOI: 10.1088/1757-899x/619/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Candlenut Shell (Alleuretus moluccana) Based Supercapacitor Electrode with Acid Electrolytes and Their Salts

Abstract: Candlenut shell was used as the precursor for activated carbon-based electrodes which prepared through two stages, namely carbonization and activation. The surface of the activated carbon was modified with HNO3. Characterization of carbons and activated carbon was performed by SEM, BET, FT-IR test and capacitance analysis using Cyclic Voltammetry. The result of SEM analysis shows that carbon pore formation has occurred after activation with H3PO4. The surface area of carbon and activated carbon determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…In Table 3 , it is observed that the capacitance of the biochars was highly random among of all them prior to and after oxidation. However, the estimated capacitance of some of the biochars are in good agreement with those reported by other authors in the literature (200 mF/g) [ 46 , 47 ]. The mango biochar demonstrated the highest capacitance values among all the biochars in H 2 at 750 °C (219.55 mF/g) and N 2 at 900 °C (273.08 mF/g), before oxidation, as seen in Table 3 and Figure 13 .…”
Section: Resultssupporting
confidence: 90%
“…In Table 3 , it is observed that the capacitance of the biochars was highly random among of all them prior to and after oxidation. However, the estimated capacitance of some of the biochars are in good agreement with those reported by other authors in the literature (200 mF/g) [ 46 , 47 ]. The mango biochar demonstrated the highest capacitance values among all the biochars in H 2 at 750 °C (219.55 mF/g) and N 2 at 900 °C (273.08 mF/g), before oxidation, as seen in Table 3 and Figure 13 .…”
Section: Resultssupporting
confidence: 90%
“…Massa elektroda juga mempengaruhi besar kecilnya nilai kapasitansi spesifik. Semakin kecil massa elektroda maka akan semakin besar pula nilai kapasitansi spesifik yang dihasilkan [17]. Nilai kapasitansi spesifik dari elektroda karbon menggunakan elektrolit 0,5 M Na 2 SO 4 .…”
Section: Hasil Dan Pembahasanunclassified